Effects of the GnRH antagonist acyline on the testis of the domestic cat (Felis catus) - Garcia Romero, Guadalupe (2012)
The aim of this study was to describe the effects of a single dose of the gonadotrophin releasing hormone 20(GnRH) antagonist acyline on testicular characteristics of the domestic cat. Twelve mature cats were 21orchidectomized unilaterally (right testis) on Day 7 (n = 7) or Day 15 (n = 5). On Day 0, 330 lg/kg acyline 22was administered SC to all the animals. Left orchidectomy was carried out on Day 15 (n = 2), Day 30 23(n = 4) and Day 60 (n = 6). Sperm were recovered from the epididymis and the testes were evaluated 24grossly, histologically and immunohistochemically. 25Significant differences (P < 0.05) were found between days for epididymal sperm motility, vigor, abnor- 26mal morphology, germinal epithelium height, spermatocytes, spermatids, spermatozoa, lumen and cellu- 27lar debris. Conversely, no significant differences were found for gross testicular and tubular 28characteristics, spermatogonia, Sertoli and Leydig cells and intertubular compartments. It was concluded 29that a single dose of acyline reversibly impaired spermiogenesis, spermatocytogenesis and sperm motil- 30ity for 2 weeks.